1995
DOI: 10.1111/j.1476-5381.1995.tb15917.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by viral respiratory infection of ovalbumin‐induced guinea‐pig tracheal hyperresponsiveness: role for tachykinins

Abstract: 1 We investigated whether virus-induced airway hyperresponsiveness in guinea-pigs could be modulated by pretreatment with capsaicin and whether viral respiratory infections could potentiate ovalbuminaerosol-induced tracheal hyperresponsiveness. 2 Animals were inoculated intratracheally with bovine parainfluenza-3 virus or control medium 7 days after treatment with capsaicin (50 mg kg-', s.c.). Four days after inoculation, tracheal contractions -were measured to increasing concentrations of substance P, histami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…A possible explanation would be that SP is a common downstream mediator in the sequence of events leading to airway hyperreactivity. In agreement with this, it has been shown that depletion of sensory neuropeptides, including SP, by capsaicin treatment prevents not only ovalbumin-induced hyperreactivity [7,8] but also hyperreactivity after platelet-activating factor [29], toluene diisocyante [30], delayed type hypersensitivity reactions [31], or respiratory viral infection [32].…”
Section: Discussionmentioning
confidence: 61%
“…A possible explanation would be that SP is a common downstream mediator in the sequence of events leading to airway hyperreactivity. In agreement with this, it has been shown that depletion of sensory neuropeptides, including SP, by capsaicin treatment prevents not only ovalbumin-induced hyperreactivity [7,8] but also hyperreactivity after platelet-activating factor [29], toluene diisocyante [30], delayed type hypersensitivity reactions [31], or respiratory viral infection [32].…”
Section: Discussionmentioning
confidence: 61%
“…In addition, capsaicin affects airway responsiveness to cholinergic agonists in guinea pigs (120). Pretreatment with capsaicin also blocks airway hyperresponsiveness induced by viruses in guinea pigs (121). This points to a role of capsaicin-sensitive sensory airway nerves in the regulation of airway responsiveness.…”
Section: Neuropeptide Depletion Studiesmentioning
confidence: 85%
“…of capsaicin, which depletes tachykinins from NANC nerves, eliminated airway hyperresponsiveness induced by acute capsaicin [48], citric acid [53], ovalbumin [54,55] toluene diisocyanate [56], endotoxin [57], plateletactivating factor (PAF) [58], respiratory viral infection [59], and ozone [60] in guinea-pigs, dinitro-fluorobenzene [61] and toluene diisocyanate [62] in mice, and Altenaria tenuis aerosol in rabbits [63].…”
Section: Involvement Of Tachykinins In Airway Hyperresponsivenessmentioning
confidence: 99%